IMPROVING STUDENTS’ VOCABULARY ABOUT HOBBIES THROUGH CHARADE GAME - Sherly Sherly; Clarry Sada; Dwi Riyanti (Universitas Tanjungpura, 2019)
AbstractThis research was aimed to know how Charade Game improved students’ vocabulary related to names of hobbies. This research was conducted in form of a Classroom Action Research in three cycles. The problems that students faced were (1) the low mastery of vocabulary and (2) the students felt bored and were hesitant. The participants of this research were 36 students in class A of the Seventh Grade Students of SMPN 14 Pontianak in Academic Year 2018/2019. The researcher used observation checklists, field notes, and individual assignment as tools to collect the data. The result showed that Charade Game improved students’ vocabulary. Students’ behavior also changed and students did not hesitate anymore while expressing the words and showed less burden while performing the vocabulary in front of the class. The mean score of students’ vocabulary also improved in every cycle. In the first cycle, the students’ mean score was 73,33. It improved to 75,27 in the second cycle, and 85,56 in the third cycle. In conclusion, Charade Game improved students’ vocabulary about name of hobbies. Keywords: Charade Game, Hobbies, Vocabulary